2010
DOI: 10.1088/0965-0393/18/3/034006
|View full text |Cite
|
Sign up to set email alerts
|

Discrete dislocation simulations of the flattening of nanoimprinted surfaces

Abstract: Simulations of rough surface flattening are performed on thin metal films whose roughness is created by nanoimprinting flat single crystals. The imprinting is carried out by means of a rigid template with equal flat contacts at varying spacing. The imprinted surfaces are subsequently flattened by a rigid platen, while the change of roughness and surface profile is computed. Attention is focused mainly on comparing the response of the film surfaces with those of identical films cleared of the dislocations and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…It was demonstrated that the proposed coupling method efficiently captures the effect of a sub-domain with discrete dislocation resolution within a crystal plasticity model for incorporating size effects in a boundary value problem with much greater computational efficiency than DDP alone. Furthermore, prior DDP analyses of indentation [34,[39][40][41][42] relied on a rigid substrate condition to simplify the computation. It was demonstrated that for an indentation depth of 0.3 m μ , the response of films of thickness 2 m μ or less exhibited a significant dependence on the substrate: a crystal plasticity representation of the substrate led to appreciably smaller indentation pressures and diminished stress and dislocation activity in the film compared to the rigid and elastic substrate representations typically used in DDP analyses of indentation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that the proposed coupling method efficiently captures the effect of a sub-domain with discrete dislocation resolution within a crystal plasticity model for incorporating size effects in a boundary value problem with much greater computational efficiency than DDP alone. Furthermore, prior DDP analyses of indentation [34,[39][40][41][42] relied on a rigid substrate condition to simplify the computation. It was demonstrated that for an indentation depth of 0.3 m μ , the response of films of thickness 2 m μ or less exhibited a significant dependence on the substrate: a crystal plasticity representation of the substrate led to appreciably smaller indentation pressures and diminished stress and dislocation activity in the film compared to the rigid and elastic substrate representations typically used in DDP analyses of indentation.…”
Section: Resultsmentioning
confidence: 99%
“…The damage due to dislocation activity in indentation processes was simulated in [38], which aimed to provide the link between the dislocation structure and the macroscopic fatigue phenomenon. Recently, Nicola and co-workers [39][40][41][42] conducted DDP simulations of the flattening of surface roughness obtained by nano-imprinting thin single crystal films. In all the aforementioned studies, the dislocation activity is studied in simplified configurations, often with the film is adhering to a rigid substrate, and these studies cannot be easily extended to scenarios in which the crystal films are adhering to or resting on polycrystalline substrates characterised by similar elastic/plastic response.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the change in contact area during loading is not easily measurable. Since the contact area evolves in a non-trivial way during contact, knowledge of the initial topography is of little use for determination of friction during contact [1]. Therefore, rough surface modeling can contribute to the prediction of friction by allowing to track the evolution of the area of contact as well as the contact pressure during loading.…”
Section: Introductionmentioning
confidence: 99%
“…The contact area is small because the surface of the Al thin film of models 1-5 is not flat. [40] Figure 4 also shows that the yield stress of the single crystal is smaller than that of the bicrystal Al thin film, and that the imprinting force of single crystal Al has an increasing process again. The disagreement between the single crystal and the bicrystal Al thin film can be attributed to the TB that hinders the slip dislocations and increases the imprinting force.…”
Section: Tb Direction Parallel To the Imprinting Directionmentioning
confidence: 91%